Research on a Novel Tooth Profile Design of Harmonic Gears Based on Improved Kinematics and Transient Dynamics - Deng Yang; He Xueming; Li Pengchao; Mu Yanming (Jixie chuandong)
To improve the meshing performance of harmonic reducers and the working performance of robots, a novel tooth profile design method for harmonic gears based on the improved kinematics and transient dynamics is proposed. Firstly, based on the characteristics of common tangent double arc tooth profile and S-type tooth profile, a new flexible tooth profile is proposed, which is the combination of S-type tooth profile and common tangent double arc tooth profile. Secondly, the tooth profile of the steel gear is calculated based on the improved kinematics method. Finally, the meshing backlash between the different tooth profiles and the stress of flexsplines without considering plastic deformation are analyzed based on the transient dynamics method. Through comparative analysis, it is found that the new tooth profile without considering plastic deformation has smaller meshing backlash and equivalent stress, the minimum meshing backlash is only 0.003 6 mm, the maximum equivalent stress under the given load condition is only 1 211.6 MPa, which are significantly lower than those of the double circular arc tooth profile flexspline, the S-shaped tooth profile flexspline, and the common tangent double circular arc tooth profile. The novel tooth profile design method can effectively improve the transmission performance of harmonic gears, which lays a theoretical foundation for the design of high-performance harmonic gears.